Community pharmacy-based medication therapy management services: financial impact for patients - Ruisinger JF; Dodson SE; Howard PA; Hare SE; Barnes BJ (Centro de Investigaciones y Publicaciones Farmaceuticas, 2012)
Objective: To determine the direct financial impact for patients resulting from Medication Therapy Management (MTM) interventions made by community pharmacists. Secondary objectives include evaluating the patient and physician acceptance rates of the community pharmacists' recommended MTM interventions.Methods: This was a retrospective observational study conducted at 20 Price Chopper and Hen House grocery store chain pharmacies in the Kansas City metro area from January 1, 2010 to December 31, 2010. Study patients were Medicare Part D beneficiaries eligible for MTM services. The primary outcome was the change in patient out-of-pocket prescription medication expense as a result of MTM services.Results: Of 128 patients included in this study, 68% experienced no out-of-pocket financial impact on their medication expenses as a result of MTM services. A total of 27% of the patients realized a cost-savings (USD440.50 per year, (SD=289.69)) while another 5% of patients saw a cost increase in out-of-pocket expense (USD255.66 per year, (SD=324.48)). The net financial impact for all 128 patients who participated in MTM services was an average savings of USD102.83 per patient per year (SD=269.18, p<0.0001). Pharmacists attempted a total of 732 recommendations; 391 (53%) were accepted by both the patient and their prescriber. A total of 341 (47%) recommendations were not accepted because of patient refusal (290, 85%) or prescriber refusal (51, 15%).Conclusions: Patient participation in MTM services reduces patient out-of-pocket medication expense. However, this savings is driven by only 32% of subjects who are experiencing a financial impact on out-of-pocket medication expense. Additionally, the majority of the pharmacists' recommended interventions (53%) were accepted by patients and prescribers.